Training in academic information system usage at Ash Shidiq Integrated Islamic Junior High School - Dawam Dwi Jatmiko Suwawi; Ibnu Asror; Yanuar Firdaus Arie Wibowo; Tora Fahrudin; Sri Astuti; Paramita Mayadewi; Alya Ghaitsa Rizky Pertiwi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Ash-Shidiq Foundation recently established the Integrated Islamic Middle School (SMP IT). Currently, the school manages academic data manually, either on paper or through spreadsheet applications. Recognizing an opportunity, the Telkom University Software Engineering Expertise Group decided to provide community service by implementing a web-based academic information system for the school. This system is hosted on a server accessible via the Internet, enabling staff, teachers, and students to access it. It aims to simplify academic data reporting for school managers. The entire community service project, from initial observation to system installation, training, video documentation, and final report preparation, spanned approximately six months. Training sessions were conducted in a classroom setting for school principals, staff, and teachers. Feedback from this community service activity showed that 25% strongly agreed, 37.5% agreed, and 37.5% were neutral regarding the suitability of the training material to partners' needs. Regarding the presentation of material, 75% strongly agreed, 25% agreed, and 50% were neutral, with 37.5% in agreement and 12.5% in disagreement about the usefulness of the technology offered.